Avoiding Getting Lost in Song Translation: The Annotated Study - Artanti, Yeni; Azhari, Azhari; Zikrullah, Muhammad; Destari, Dinda (OKARA: Jurnal Bahasa dan Sastra, 2025)
The rapid advancement of digital technology has led many texts to be freely translated by anyone or anything, including machine translation, without paying attention to the context or linguistic rules, resulting in misleadingly translated texts. Technological advances that allow everyone to have free access to anything have made it easy for anyone to obtain texts. The study used annotated translations to correct the misleading renderings of Putri Ariani’s songs, "Loneliness" and "Perfect Liar." The research utilized a qualitative research design. Data was obtained from the song lyrics. Dictionaries, scientific articles, literary works, reports, books, and other reliable documents provide the data for annotation. We analyzed the data using a translation approach that prioritizes the target text and annotations. The researchers discovered that the annotated literal translation strategy could provide a precise, good, accurate, comparable, and clear reference to the translation of the text or lyrics of Putri Ariani’s Loneliness and Perfect Liar. The translation can also serve as a reference for the correct translation of the songs, as it is based on a reliable foundation. It concluded that annotated translation is more contextually accurate and not misleading. Readers of the translated song lyrics need to clarify and think critically to avoid taking them for granted.